An Outbreak of Respiratory Viral Infections in a Professional Ice Hockey Team - Grönroos, Wilma; Helenius, Petri; Valtonen, Maarit; Waris, Matti; Heinonen, Olli J.; Ruuskanen, Olli (Wiley, 2025)
Background: Viral acute respiratory infections (ARIs) are an important cause of illness in athletes. However, their impact on ice hockey players is unclear.
Method: We describe an outbreak of ARIs in a professional ice hockey team.
Results: Contrary to expected influenza, the 40-day outbreak was caused by 8 different respiratory viruses, that is, 2 different influenza A viruses, human coronavirus-NL63 (HCoV-NL63), respiratory syncytial viruses (RSV) A and B, 2 different rhinoviruses, enterovirus D68, and parainfluenza type 2 virus.
Conclusion: Only influenza A and HCoV-NL63 were possibly spread within the team thus suggesting an important contraction from the community. The burden of illness was substantial.